2018
DOI: 10.1186/s40462-017-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal migration patterns between natal locations of ruby-throated hummingbirds (Archilochus colubris) and their Gulf Coast stopover site

Abstract: BackgroundAutumn latitudinal migrations generally exhibit one of two different temporal migration patterns: type 1 where southern populations migrate south before northern populations, or type 2 where northern populations overtake southern populations en route. The ruby-throated hummingbird (Archilochus colubris) is a species with an expansive breeding range, which allows opportunities to examine variation in the timing of migration. Our objective was to determine a relationship between natal origin of ruby-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This can be considered equivalent to the role of Impatiens biflora flowers for the fall migration of the Ruby-Throated Hummingbird ( Archilochus colubris ); the peak in flowering times of I. biflora is closely related to the peak migration time of the Ruby-Throated Hummingbird throughout the eastern United States ( Bertin, 1982 ). However, recent studies found that the correlation in phenology between Ruby-Throated Hummingbirds and I. biflora is not supported in southern breeding individuals in United States ( Zenzal et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be considered equivalent to the role of Impatiens biflora flowers for the fall migration of the Ruby-Throated Hummingbird ( Archilochus colubris ); the peak in flowering times of I. biflora is closely related to the peak migration time of the Ruby-Throated Hummingbird throughout the eastern United States ( Bertin, 1982 ). However, recent studies found that the correlation in phenology between Ruby-Throated Hummingbirds and I. biflora is not supported in southern breeding individuals in United States ( Zenzal et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hawk was then startled and took the hummingbird in its bill and flew back into the tree line where it was originally perched and finished consuming the hummingbird. We suspect the hummingbirds were either on stopover or initiating migration (i.e., engaged in hyperphagia) given the high levels of competition and previous research finding that Ruby-throated Hummingbirds are on stopover as early as 26 August in coastal Alabama (Zenzal and Moore 2016, Zenzal et al 2018), which is south of the location where this observation was made.…”
Section: Observationmentioning
confidence: 90%
“…Stable isotope ratios of hydrogen, carbon, and nitrogen, extracted from inert animal tissues, such as claws and feathers, reflect the isotope ratios in the environment where those tissues were grown and can provide inferences about large-scale animal movements and diet preferences in species with small body size (Rubenstein and Hobson, 2004; Zenzal et al, 2018; Vander Zanden et al, 2018). However, a clear advantage of adopting a multi-element stable isotope approach is that migrants can be assigned to different breeding and molting grounds of origin while their diet preferences are also revealed and clustered in trophic guilds (Herrera et al, 2003).…”
Section: Discussionmentioning
confidence: 99%